2016
DOI: 10.1177/0165551515610513
|View full text |Cite
|
Sign up to set email alerts
|

Arabic tweets sentiment analysis – a hybrid scheme

Abstract: The fact that people freely express their opinions and ideas in no more than 140 characters makes Twitter one of the most prevalent social networking websites in the world. Being popular in Saudi Arabia, we believe that tweets are a good source to capture the public’s sentiment, especially since the country is in a fractious region. Going over the challenges and the difficulties that the Arabic tweets present – using Saudi Arabia as a basis – we propose our solution. A typical problem is the practice of tweeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(55 citation statements)
references
References 25 publications
0
50
0
Order By: Relevance
“…In the proposed approach, the authors linked an Arabic morphological analyzer Aramorph lexicon with Senti-WordNet and included MSA only. For Saudi dialect, there are some proposed lexicons such as Adayel and Azmi [4] for Saudi dialect lexicon. This lexicon contains only around 1500 terms.…”
Section: Sentiment Lexicon Constructionmentioning
confidence: 99%
“…In the proposed approach, the authors linked an Arabic morphological analyzer Aramorph lexicon with Senti-WordNet and included MSA only. For Saudi dialect, there are some proposed lexicons such as Adayel and Azmi [4] for Saudi dialect lexicon. This lexicon contains only around 1500 terms.…”
Section: Sentiment Lexicon Constructionmentioning
confidence: 99%
“…The proposed polarity update method improves on the approach presented by Aldayel and Azmi () by using switch and switch‐neutral methods for changing the polarity of a term used in tweets. The authors of Aldayel and Azmi () used a supervised learning technique for updating the polarity of words in reviews, whereas we compute the new sentiment score of a term using a revised scheme of (a) polarity switching, (b) neutral switching, and (c) term weighting. This enhancement contributes significantly to the accurate scoring of domain‐specific words, as reported in the results and evaluation section.…”
Section: Methodsmentioning
confidence: 99%
“…The recent studies (Aldayel & Azmi, 2016;Asghar, Ahmad, Qasim, Zahra, & Kundi, 2016;Duwairi & El-Orfali, 2014;Ikeda, Takamura, Ratinov, & Okumura, 2008) have demonstrated that their sentiment update methods produce promising results with respect to accurate scoring of domainspecific words in the sentiment analysis of user reviews. They achieved significant improvement in accuracy in both the hotel and movie domains.…”
Section: Updating a Term's Sentiment Scorementioning
confidence: 99%
“…It provide several advantages such as improved process flow, reduced inventories, better data analysis, better customer service, better enterprise performance and higher efficiency. All of these attract organizations to adopt ERP systems to strongly enter the competitive market [5]. A successful ERP implementation needs a long time and high recourse to be acquired.…”
Section: Enterprise Resource Planning (Erp)mentioning
confidence: 99%